Parent-only Interventions for Anxiety Disorders in Children and Adolescents - Peng, Shuangshuang; Zhong, Yijuan (Journal of Contemporary Medical Practice, 2025)
Psychotherapy for anxiety disorders in children and adolescents is mostly child-focused treatment, with less attention paid to parental involvement. The important role that parents play in the development, maintenance, and treatment of anxiety disorders in children and adolescents makes parent-only intervention an effective alternative when treatments targeting children and adolescents are inaccessible or ineffective. This article reviews several parent-only interventions for anxiety disorders in children and adolescents that are commonly used in current clinical research and practice, as well as their effectiveness, settings, and procedures, and provides a vision for future research and practice in the hope of informing the development of treatments for anxiety disorders in children and adolescents.